KEPENTINGAN JEPANG MELAKUKAN KERJASAMA BIDANG PERTAHANAN DALAM MALABAR EXERCISE DENGAN AMERIKA SERIKAT DAN INDIA - Windyaro Pramana Lahagu; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The collaboration of the Malabar Naval Exercise was initially a bilateral cooperation between the US and India which was first held in 1992. This collaboration is a defense cooperation in the maritime field carried out by the US Navy and the Indian Navy. In the implementation of the Malabar Exercise that carried out by the US and India, Japan has participated three times in this cooperation in 2007, 2009 and 2014. In 2015, India invited Japan to become a permanent partner in Malabar Exercise and make this collaboration a Trilateral cooperation between Japan, US and India. This study analyzes Japan interests in Malabar Exercise cooperation in the period 2015-2017. The purpose of this study is to find out what Japan interest in the Malabar Exercise cooperation in period 2015-2017. The Research from this paper uses qualitative research methods with data collected through literature studies. The theory used in this paper is international cooperation theory, while the concept that used is the national interest consept. Key words : Malabar Exercise, Security, Japan, Defense Cooperation